Actionability of HER2-amplified circulating tumor cells in HER2-negative metastatic breast cancer: the CirCe T-DM1 trial - William Jacot; Paul Cottu; Frederique Berger; Coraline Dubot; Laurence Venat-Bouvet; Alain Lortholary; Hugues Bourgeois; Marc Bollet; Veronique Servent; Elisabeth Luporsi; Marc Espié; Severine Guiu; et al. (Breast Cancer Research, 2019)
Abstract Background In this prospective phase 2 trial, we assessed the efficacy of trastuzumab-emtansine (T-DM1) in HER2-negative metastatic breast cancer (MBC) patients with HER2-positive CTC. Methods Main inclusion criteria for screening were as follows: women with HER2-negative MBC treated with ≥ 2 prior lines of chemotherapy and measurable disease. CTC with a HER2/CEP17 ratio of ≥ 2.2 by fluorescent in situ hybridization (CellSearch) were considered to be HER2-amplified (HER2 amp ). Patients with ≥ 1 HER2 amp CTC were eligible for the treatment phase (T-DM1 monotherapy). The primary endpoint was the overall response rate. Results In 154 screened patients, ≥ 1 and ≥ 5 CTC/7.5 ml of blood were detected in N = 118 (78.7%) and N = 86 (57.3%) patients, respectively. ≥1 HER2 amp CTC was found in 14 patients (9.1% of patients with ≥ 1 CTC/7.5 ml). Among 11 patients treated with T-DM1, one achieved a confirmed partial response. Four patients had a stable disease as best response. Median PFS was 4.8 months while median OS was 9.5 months. Conclusions CTC with HER2 amplification can be detected in a limited subset of HER2-negative MBC patients. Treatment with T-DM1 achieved a partial response in only one patient. Trial registration NCT01975142, Registered 03 November 2013